KESADARAN PERSEPSI TENTANG KEADILAN DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK RESTORAN DI KOTA PALU - Ni Nyoman Kristian Mediawati (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Tax Compliance issue is a constraint in optimizing tax revenue. Tax compliance is the main thing that supports the course of the selfassessment system which in this system obligatory role of the taxpayer is required to realize the achievement of tax revenue. Through optimal effort, DPPKAD always trying to explore the potential tax revenue by raising awareness, public facilities and the quality of their fulfillment of tax services. This study focuses on the awareness of the taxpayer based on the research Suryadi (2008). Perceptions of fairness based on the research that has been conducted by Saad (2009). Tax and service quality based on the research that has been done by Umaimah (2011). This study uses multiple linear regression with taxpayer data obtained from the Office of Financial Management Services Regional Asset registered until 2013. This study proves that the awareness, perceptions of fairness and quality of service significant and positive impact on tax compliance restaurants in the city of Palu